God, humanity, and history : the Hebrew First Crusade narratives - Chazan, Robert (Berkeley, CA : University of California Press, 2000)
Closely focused on the Hebrew First-Crusade narratives, this text examines the three surviving accounts of the crusaders assaults on the Rhineland Jewish communities in 1096. These accounts are compared with earlier Jewish history writing and with contemporary crusade historiography.
Chapter Eight: The Historicity of the Hebrew NarrativesChapter Nine: The Hebrew First Crusade Narratives: The Timeless; Chapter Ten: God, Humanity, and History; Chapter Eleven: Comparative Dimensions: The 1096 Narratives and Classical Jewish Tradition; Chapter Twelve: Comparative Dimensions: The 1096 Narratives and Their Medieval Setting; Epilogue; Appendix; Abbreviations; Notes; Bibliography; Index
Includes bibliographical references (pages 257-262) and index.
Print version record.
English.
JSTOR
Keywords: Jews -- Germany -- History -- 1096-1147 -- Sources; Jews -- Persecutions -- Germany -- History -- Sources; Jewish martyrs -- Germany -- Biography -- Sources; Crusades -- First, 1096-1099 -- Sources; Germany -- Ethnic relations -- Sources; Juifs -- Allemagne -- Histoire -- 1096-1147 -- Sources; Juifs -- Persécutions -- Allemagne -- Histoire -- Sources; Martyrs juifs -- Allemagne -- Biographies -- Sources; Croisades -- 1re croisade, 1096-1099 -- Sources; HISTORY; RELIGION -- Judaism -- General; Crusades; Ethnic relations; Jews; Jews -- Persecutions; Germany; Joden; Kruistochten; Kronieken (geschiedenis); Rheinland; 1096-1147; Biography; Biographies; History; Sources; Biographies; Biographies